Home range analysis of the semi-resident Bottlenose dolphin (Tursiops truncatus) population of Cardigan Bay (Wales) - Correia, Ana Rita Mendes Pinheiro (2018)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2017